Association between single limb standing test results and healthcare costs among community-dwelling older adults. (January 2021) - Tominaga, Ryoji; Yamazaki, Shin; Fukuma, Shingo; Goto, Rei; Sekiguchi, Miho; Otani, Koji; Iwabuchi, Masumi; Shirado, Osamu; Fukuhara, Shunichi; Konno, Shin-ichi
Highlights: Results of the single limb standing test were related to healthcare costs. Participants who could stand on a single limb for 30 s had lower costs. The single limb standing test may identify people needing many healthcare services. Abstract: Background and objective: Identifying risks for older adults who will require healthcare resources is critical for the government, healthcare providers, and consumers. The objective of this study was to examine the relationship between the results of the single limb standing (SLS) test and healthcare costs among community-dwelling older adults. Methods: We used data obtained from a population-based prospective cohort study of the residents of Tadami town in Fukushima Prefecture, Japan. The participants were above 60 years of age and had undergone annual health check-ups, and data on their healthcare costs over the two-year study period were available. A censored regression model adjusted for potential confounders was used to estimate the mean difference in total healthcare costs between participants who could remain standing on a single limb for at least 30 s and those who could not. Results: Healthcare costs of participants who passed the SLS test were significantly lower than those who did not. The mean difference between the two groups' healthcare costs was 4064 USD (95 % confidence interval: 2661–5467 USD, p < 0.05). After adjusting for potential confounders, the mean difference between the two groups was smaller (1686 USD) but remained statistically significant (95 % confidence interval: 125–3246 USD, p < 0.05). Conclusions: Among community-dwelling older adults, limited static balance (SLS time <30 s) was found to be associated with high healthcare costs in the two years after the SLS test. The SLS test may help identify individuals at high risk of becoming frequent users of healthcare services in the future.